Salvia miltiorrhiza Bunge (Danshen) and Bioactive Compound Tanshinone IIA Alleviates Cisplatin-Induced Acute Kidney Injury Through Regulating PXR/NF-κB Signaling - Dou, Jing-Yun; Zhang, Min; Cen, Huan; Chen, Yi-Qin; Wu, Yi-Fan; Lu, Fuhua; Zhou, Jiuyao; Liu, Xu-Sheng; Gu, Yue-Yu (Frontiers in Pharmacology, 2022)
Objective The present study aims to provide evidence on the potential protective role of Salvia miltiorrhiza Bunge (Danshen) and its bioactive compound Tanshinone IIA (TanIIA) in AKI and to reveal the specific regulatory function of PXR/NF-κB signaling in AKI-induced renal inflammation. Methods Network pharmacological analysis was used to study target genes and regulatory networks in treating Salvia miltiorrhiza on AKI. Further experiments with in vivo AKI mouse model and in vitro studies were applied to investigate the renal protective effect of TanIIA in AKI. The mechanisms of TanIIA regulating PXR/NF-κB signaling in renal inflammation were also studied. Results Network pharmacology had suggested the nuclear receptor family as new therapeutic targets of Salvia miltiorrhiza in AKI treatment. The in vivo studies had demonstrated that TanIIA improved renal function and inflammation by reducing necrosis and promoting the proliferation of tubular epithelial cells. Improved renal arterial perfusion in AKI mice with TanIIA treatment was also recorded by ultrasonography. In vitro studies had shown that TanIIA ameliorated renal inflammation by activating PXR while inhibiting PXR-mediated NF-κB signaling. The results have suggested a role of PXR activation against AKI-induced renal inflammation. Conclusion Salvia miltiorrhiza Bunge (Danshen) may protect kidneys against AKI by regulating nuclear receptors. TanIIA improved cell necrosis proliferation and reduced renal inflammation by upregulating the expression of PXR and inhibiting NF-κB signaling in a PXR-dependent manner. PXR may be a potential therapeutic target for AKI treatment.